Structural Fold and Binding Sites of the Human Na(+)-Phosphate Cotransporter NaPi-II - Fenollar-Ferrer, Cristina (The Biophysical Society, 2014)
Phosphate plays essential biological roles and its plasma level in humans requires tight control to avoid bone loss (insufficiency) or vascular calcification (excess). Intestinal absorption and renal reabsorption of phosphate are mediated by members of the SLC34 family of sodium-coupled transporters (NaPi-IIa,b,c) whose membrane expression is regulated by various hormones, circulating proteins, and phosphate itself. Consequently, NaPi-II proteins are also potentially important pharmaceutical targets for controlling phosphate levels. Their crucial role in P(i) homeostasis is underscored by pathologies resulting from naturally occurring SLC34 mutations and SLC34 knockout animals. SLC34 isoforms have been extensively studied with respect to transport mechanism and structure-function relationships; however, the three-dimensional structure is unknown. All SLC34 transporters share a duplicated motif comprising a glutamine followed by a stretch of threonine or serine residues, suggesting the presence of structural repeats as found in other transporter families. Nevertheless, standard bioinformatic approaches fail to clearly identify a suitable template for molecular modeling. Here, we used hydrophobicity profiles and hidden Markov models to define a structural repeat common to all SLC34 isoforms. Similar approaches identify a relationship with the core regions in a crystal structure of Vibrio cholerae Na(+)-dicarboxylate transporter VcINDY, from which we generated a homology model of human NaPi-IIa. The aforementioned SLC34 motifs in each repeat localize to the center of the model, and were predicted to form Na(+) and P(i) coordination sites. Functional relevance of key amino acids was confirmed by biochemical and electrophysiological analysis of expressed, mutated transporters. Moreover, the validity of the predicted architecture is corroborated by extensive published structure-function studies. The model provides key information for elucidating the transport mechanism and predicts candidate substrate binding sites.